THE KOMBINASI INTERVENSI TERAPI LATIHAN DAN ULTRASOUND (US) LEBIH BAIK DARIPADA MASASE DAN ULTRASOUND (US) UNTUK PENURUNAN NYERI PADA KONDISI PLANTAR FASCITIS - Rica, Theresia (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 2 (2013): Majalah Ilmiah Fisioterapi Indonesia, 2013)
Plantar Fascitis is disease hitting system of muskulus skeletal and influenced by some factor for example : age, heavy of body, trauma, and actifity. While form manifestasinya is the growing of bone of at area calcaneus. People with osteoarthritis in general complain the existence of pain in bone and limitation of motion. The aim of this research is to know pain in bone rate of change at patient of plantar fascitis. Because pain in bone have the character of objectively, hence utilized measuring instrument namely Verbal Rating Scale (VRS). Therefore, this research wishes to prove technical of therapy combination which is resulting degradation of better pain in bone of patient of Osteoarthritis k. Such combination is massage (second treatment) and US with Exercise therapy (first treatment) and US with frequency 5x each; every 2-3 day once. This Research device have the character of experimental with device of randomized pre test post and test design group controlled, where intake of sample of population conducted at random also the division of sample become two group is also conducted at random by using is techniques of permuted sampling block. Research Subject are all patient of pain in calcaneus bone effect of osteoarthritis through procedure of assessment physiotherapy which have been specified in Clinic Physiotherapy on Jl. Tukad Banyusari No. 5 Panjer Denpasar-Bali. Meaning analysis with test of t-paired (couple) indicate that at each group yield degradation of sigh of pain in bone of plantar fascitis after treatment differ by having a meaning of (p < 0,05). While different Test of therapy is second of group after treatment aim to compare average sigh of pain in bone of plantar fascitis, analyze meaning with test of tindependent (not on couple) indicating that value of t = 2,34 and value of p = 0,04. Matter this means that is second of group of average sigh of pain in bone at patient of plantar fascitis after treatment differ by having a meaning of (p < 0,05). Pursuant to percentage of average degradation of sigh of pain in bone of plantar fascitis at indicating that percentage of average degradation of sigh of pain in bone of plantar fascitis at group one 82,67% bigger than group two 60,47%. There by can be said by treatment of group one that is therapy combination exercise therapy and US can degrade sigh of pain in bone at patient of compared to better plantar fascitis of treatment of group two namely with giving combination and massage of US.
Keywords: Exercise therapy, massage and US, plantar fascitis.